Effect of different smoking processes on the sensory and chemical attributes of two shrimps native to Brazil (Research, Society and Development, 2020)
The effects of smoking processes on the sensory and proximate components of two species of shrimp were evaluated. Sixty specimens of each species were distributed in a completely randomized design, with two treatments (T1 = hot smoking and T2 = liquid smoking), and fresh shrimps samples were used as control (T3). The sensory characteristics were evaluated using the 9 point hedonic scale and the acceptance index. The centesimal composition was evaluated based on 100 g from each treatment and the fresh samples. The data were submitted to one-way ANOVA and Tukey's test. The results of sensory analysis showed significant variations (p 0,05). The acceptance rate was above 70% for amazonian prawn and 80% for white shrimp, regardless of the smoking method. The proximate analysis showed significant differences between the two smoking processes, hot and liquid, with moderet values of lipids, between 0.27% and 1.51%, and high protein values, of 24.61% 24.13%, for white shrimp and amazonian prawn, respectively. The smoking processes altered the sensory and chemical profile of the prawns, causing good acceptance and adequate nutritional constitution for smoked fish.